Expression profile of pattern recognition receptors in skeletal muscle of SOD1(G93A) amyotrophic lateral sclerosis (ALS) mice and sporadic ALS patients. (16th April 2018) - Lehmann, S.; Esch, E.; Hartmann, P.; Goswami, A.; Nikolin, S.; Weis, J.; Beyer, C.; Johann, S.
Abstract : Aims: Amyotrophic lateral sclerosis (ALS) is characterized by degeneration of motoneurons and progressive muscle wasting. Inflammatory processes, mediated by non‐neuronal cells, such as glial cells, are known to contribute to disease progression. Inflammasomes consist of pattern recognition receptors (PRRs), apoptosis‐associated speck‐like protein (ASC) and caspase 1 and are essential for interleukin (IL) processing and a rapid immune response after tissue damage. Recently, we described inflammasome activation in the spinal cord of ALS patients and in SOD1 (G93A) ALS mice. Since pathological changes in the skeletal muscle are early events in ALS, we hypothesized that PRRs might be abnormally expressed in muscle fibre degeneration. Methods: Western blot analysis, real‐time PCR and immunohistochemistry were performed with muscle tissue from presymptomatic and early‐symptomatic male SOD1 (G93A) mice and with muscle biopsies of control and sporadic ALS (sALS) patients. Analysed PRRs include nucleotide‐binding oligomerization domain‐like (NOD‐like) receptor protein 1 (NLRP1), NLR protein 3 (NLRP3), NLR family CARD domain‐containing 4 (NLRC4) and absent in melanoma 2. Additionally, expression levels of ASC, caspase 1, interleukin 1 beta (IL1β) and interleukin 18 (IL18) were evaluated. Results: Expression of PRRs and ASC was detected in murine and human tissue. The PRR NLRC4, caspase 1 and IL1β were significantly elevated in denervated muscle of SOD1 (G93A) mice and sALS patients. Furthermore, levels of caspase 1 and IL1β were already increased in presymptomatic animals. Conclusion: Our findings suggest that increased inflammasome activation may be involved in skeletal muscle pathology in ALS. Furthermore, elevated levels of NLRC4, caspase 1 and IL1β reflect early changes in the skeletal muscle and may contribute to the denervation process.